The impacts of breast and cervical cancer in a community setting are predictors of the quality of life of family caregivers - Ahmad aminudin (Symbiohealth, 2023)
their families at home. Globally, there is a growing governmental policy to engage caregivers, families, and communities in the healthcare delivery system. Family caregivers (FCG) have taken responsibility for the day-to-day care of their ill loved ones at home. A cancer diagnosis is a major event for the person diagnosed and also for his or her family and caregivers. The caregiving activity has a significant impact on FCG’s quality of life (QOL). This study aimed to analyze the best predictor of FCG’s QOL of female cancer patients in a community setting. Methods: This cross-sectional study involved five Public Health Centers (PHCs) among 63 PHCs in Surabaya (7.94%), Indonesia, which were selected by one-stage cluster random sampling. There were 60 FCGs of female cancer patients who participated in this study (n = 60). The Caregiver Quality of Life – Cancer (CQOLC) was a valid and reliable instrument that was used to collect the data. Linear regression and one-way ANOVA tests were used in data analysis (α < .05). Ethical clearance was issued. Results: Most respondents were middle-aged married men with sufficient educational background and still actively working with sufficient income. Their QOL was mostly at a moderate level (Mean ± SD = 62.57 ± 16.23). Burden (p < 0.000), disruptiveness (p = 0.001), and financial concern (p < 0.000) were significantly different between the low, moderate, and high FCG’s QOL. The best predictor of FCG’s QOL of female cancer patients in a community setting was disruptiveness (R2 = 0.622; p < 0.000) compared to burden (R2 = 0.531; p < 0.000) and financial concern (R2 = 0.184; p = 0.001), especially when other family members have not shown interest in caregiving (R2 = 0.539; p < 0.000). Conclusions: FCG’s QOL of female cancer patients in a community setting is at a moderate level. Disruptiveness, burden, and financial concern could predict FCG’s QOL significantly. The other family members’ disinterest in caregiving which belongs to the disruptiveness domain is the best predictor of FCG’s QOL of female cancer patients in a community setting, which accounted for 53.9% variance of QOL in this population.